Solanum glaucophyllum intoxication in goats: Case study - Barale, Joaquín; Ovelar, Florencia; Lázaro, Fermín; Scioli, Maria Valeria; Canton, German Jose; Garcia, Juan Agustin (Elsevier, 2024)
Solanum glaucophyllum is a toxic plant with calcinogenic effect that causes enzootic calcinosis (EC) characterized by soft tissue metastatic mineralization mainly in cattle and rarely sheep, buffaloes, pigs, horses, and goats. We describe an outbreak of EC in a herd of 64 goats due to S. glaucophyllum consumption. Thirty-four goats were affected exhibiting hirsutism, stiffening, kyphosis and emaciation. Twelve goats died. Grossly, tissue mineralization was observed in the aorta and carotid arteries, lungs, and heart. Lesions were characterized by multiple rough white plaques, and hardened tissues with loss of elasticity. Microscopically, multisystemic mineralization was observed in aorta and carotid arteries, heart, lung, abomasum, intestine, spleen, lymph nodes, kidney, spleen, and meninges, characterized by extensive granular basophilic deposits of tunica media and/or intima of blood vessels; confirmed as calcium salt deposits with Von Kossa stain. We conclude that ingestion of S. glaucophyllum can cause EC in goats. Though EC is rare in goats under some conditions such as heavy drought and abundant S. glaucophyllum exposure disease can develop.